A New Photovoltaic Energy Sharing System between Homes in Standalone Areas - A. Mezouari; R. Elgouri; M. Igouzal; M. Alareqi; K. Mateur; H. Dahou; L. Hlou (Institute of Advanced Engineering and Science, 2018)
Today, global energy consumption is dominated by fossil fuels such as oil, coal and gas. The intensive consumption of these energy sources gives rise to greenhouse gas emissions and therefore an increase in CO2 emissions. Photovoltaic energy has persistently been considered as a green and pollution-free renewable energy source to overcome greenhouse effect and energy crisis. This paper describes a new method of photovoltaic energy sharing in standalone micro-grids using photovoltaic panels. This approach is based on automatic electrical energy sharing depending on the state of charge (SOC) of the electrical storage unit using by each home and on the electrical power consumption of each home.The monitoring system is connected to each home in micro-grid, it manage each home’s energy use, and assigns more energy to a large energy-consuming home. This architecture contributes to reducing total energy lost.